Study on Safety Control of Large-Section Roadway with High Stress and Broken Surrounding Rock - Wen-qing Peng; Hao Zhu; Qi Wang; Gang Peng (Advances in Civil Engineering)
In order to solve the problem of difficult support of the roadway with high stress and large-section broken surrounding rock, this paper takes the subinclined shaft in Gaokeng mine of Jiangxi Province as the engineering background, analyzes the deformation mechanism and support mode of the roadway under the influence of mining through field investigation and mechanical derivation, and concludes that the stress concentration point of the roadway is in the middle point of roof and floor and the middle point of left and right sides. Through the modeling analysis of FLAC3D numerical software and the comparison of various support schemes, it is concluded that, after the combined support method of “anchor, net, and spray + grouting + full-section anchor cable + floor anchor cable“ is adopted, the convergence of roof and floor is reduced by 508 mm, and the convergence of two sides is reduced by 663 mm. And, it is applied in engineering practice. The results show that the combined support scheme can effectively control the stability of the surrounding rock.